Effect of different extraction methods on yield and quality of araticum (Annona crassiflora Mart.) seed oil - BRAGA, Lucas Pereira; AMORIM, Katiúcia Alves; GOULART, Gilberto Alessandre Soares; ASQUIERI, Eduardo Ramirez; DAMIANI, Clarissa (Food Science and Technology, 2024)
Microwave- and ultrasound-assisted extraction methods can increase the yield and quality of oil extraction. This study investigated their effects on araticum seed oil extraction compared with conventional methods. Oils were extracted using press and Soxhlet techniques, combined with microwave- and ultrasound-assisted methods at different times. Key parameters such as yield, acidity index, peroxide index, iodine index, moisture, saponification index, ether-insoluble impurities, antioxidant activity by DPPH and ABTS methods, and fatty acid profile were evaluated. The highest oil yield (24.22%) was achieved by combining the press with Soxhlet. Based on EC50 values, antioxidant activities ranged from 1.06 ± 0.10 to 5.19 ± 0.39 mg/mL and 2.26 ± 0.33 to 10.43 ± 0.28 µM trolox/g for DPPH and ABTS, respectively. The ultrasound-assisted method showcased superior antioxidant activity. Predominant fatty acids included oleic, linoleic, palmitic, and stearic acids. Extractions by ultrasound-assisted press at 15 and 30 min showed enhanced antioxidant potency and reduced peroxide and acidity indices. The extraction method affected the characteristics of the oil, and changes in the fatty acid profile were observed. Non-heating methods yielded more unsaturated acids but with low extraction yield.